A DESCRIPTIVE STUDY ON TEACHING SPEAKING OF RECOUNT TEXT BASED ON SCHOOL LEVEL-BASED CURRICULUM AT THE EIGHT YEAROF SMP N 6 WONOGIRI IN 2009/2010 ACADEMIC YEAR - FAJARWATI, ARIEFIKA (2010)
This research paper aims at describing the implementation of study on teaching speaking of recount text and identifying the problems faced by the teacher and the students on teaching speaking of recount text based on school level-based curriculum at the eight year of SMP N 6 WONOGIRI. This research belongs qualitative research, which does not use statistic data. The research was conducted at SMP N 6 Wonogiri and the writer used four ways to collect the data, namely: library study, observation, interview, and document analysis. The data of this research are interview script, field notes, lesson plan and the sources of the data, namely: event, respondents, and documents. The results of the study show that: 1) The goals on teaching speaking of recount text based on school level-based curriculum at the eight year in SMP N 6 WONOGIRI are to develop the students' courage to speak English in front of the audience, to improve speaking skill, especially for the students in recount text lesson, and to make the students understand recount text in English lesson, especially in English speaking. 2) The strategies in speaking activity of recount text applied by the teacher are using the group work, making a careful choice of topic and giving tasks to stimulate interest, giving some instructions or training in discussion skills, and keeping students to speak the target language. 3) The syllabus of English lesson is designed and is arranged by the teacher. The teacher does not only use text book as the source of material but also uses a work sheet to make the students understand the material more. 4) The classroom activities on teaching speaking of recount text are describing picture and interviewing. 5) To guarantee the effectiveness of students' achievement in performing the speaking, the teacher takes four steps, namely: BKOF (Building Knowledge of Field), MOT (Modeling of Text), JCOT (Joint Construction of Text), and ICOT (Individual Construction of Text). 6) The problems faced by the teacher on teaching speaking are classroom management, limited time, different capability in receiving the materials each student, and differences of the parents' economic and educational background of the students. 7) The problems faced by the students on teaching speaking of recount text are limited vocabulary, pronunciation, grammar, the performance, and nervousness.